Interactive Effect of Irrigation Skipping and Salicylic Acid on Growth of Sunflower (Helianthus annuus L.) - Shorsh Hussein Bapir; Saber Wasman Hamad (Zanco Journal of Pure and Applied Sciences, 2023)
Under the semiarid, in the Sulaimani Region, two sites (Rnaya City and Qaladza City) were chosen to conduct the research during the summer season. It was designed as a split plot factorial arrangement using randomized complete block design (RCBD) with three replications at both locations. The purpose of this experiment was to determine the skipping irrigating effect I1, I2, and I3 with salicylic acid applied S1 and non-applied S0 on the sunflower growth at three different growth stages (vegetative, flowering, and achene-forming stages), and compared to the effects of full irrigation I4. Complete irrigation with salicylic acid applied resulted in the best growth, while the lowest growth was recorded by skipping irrigation without salicylic acid application at the flowering stage. The treatments without salicylic acid application were found to be the most effective in conditions of low watering. Moreover, there was a failure in flowering stage and increasing growth when watering was missed, compared to the vegetative and achene stages. Consequently, it is concluded that avoiding limiting irrigation during the flowering stages can lead to have a better production.